(untitled) (BioLaw Journal - Rivista di BioDiritto, 2019)
In New Zealand, an AI called Sam is “preparing” – according to its creators – to run for a seat in the next general election. The idea of a total or partial replacement of the political decision-maker with an AI raises, of course, an innumerable series of questions. Firstly, the transparency of the decision-making process itself: who has designed the (algorithmic?) infrastructure, and who can influence it? With what data has it been fed? Does it use machine learning techniques? This idea lends itself easily to an anti-political and – in particular – anti-parliamentary use, both in the form of technocratic extremism and of an exquisitely “populist” message in terms of brutal simplification of a complex decision-making process. This kind of replacement is still a sort of Swiftian provocation: however, it already allows to question what is commonly perceived as lacking in the mechanisms of representative democracy.